PENINGKATAN KAPASITAS KADER DAN IBU HAMIL MELALUI EDUKASI KOMPLEMENTER UNTUK PERAWATAN IBU HAMIL DAN NIFAS - Nugrawati, Nelly Nugrawati; Ekawati, Nur; Wijaya, Ayu; Adam, Andi Muhammad (Jurnal LENTERA, 2025)
Maternal health during pregnancy and the postpartum period requires special attention, particularly in areas with limited access to health services such as Patimpeng Subdistrict. This community service program aimed to improve the capacity of health cadres and empower pregnant women through education on complementary care practices. The methods included socialization, counseling, hands-on training, as well as monitoring and evaluation. The training covered oxytocin massage techniques, the use of lavender aromatherapy, and the preparation of herbal galactagogues. Participants consisted of 20 health cadres and 15 pregnant women. The results showed an increase in participants’ knowledge, from 11% to 74% in the "good" category, and in skills, from 14% to 66% after training. Cadre logbooks indicated sustained implementation of the practices in the community. This activity proved effective in enhancing the knowledge and skills of cadres and providing comfort to pregnant women through applicable, low-cost, and sustainable non-pharmacological approaches.